Sustainable Livestock Farming for Improving Socio-Economic Condition - Shamsuddoha, Mohammad; Quaddus, Mohammed; Klass, Desmond (Institute for Research and Community Service, Petra Christian University, 2013)
Sustainability is most effective concept to improve socio-economic condition including environment. Constructive socioeconomic changes are getting priority in recent years among academia and business sector in Bangladesh. Bangladesh poultry sub-sector has long supply chains having associated with various stakeholders. In this paper, a case poultry farm was taken to examine sustainable production process that links with socio economic benefits. Design science method under quantitative paradigm was chosen to develop a sustainable model for the case industry. A Simulation model was developed using simul8 software to construct the real poultry operation. The objectives of this paper are to construct sustainable model for the poultry industry along with socio-economic issues. Later, simulated model output will examine it through various performance indicators (KPIs) to find out the impacts on socio-economic benefits. Numbers of KPIs have been briefly discussed in light of research problem to illustrate positive effects of sustainable production.